Mineralization enhancement of a recalcitrant pharmaceutical pollutant in water by advanced oxidation hybrid processes (2009)
ABSTRACT: Degradation of the biorecalcitrant pharmaceutical micropollutant ibuprofen (IBP) was carried out by means of several advanced oxidation hybrid configurations. TiO2 photocatalysis, photo-Fenton and sonolysis – all of them under solar simulated illumination – were tested in the hybrid systems: sonophoto-Fenton (FS), sonophotocatalysis (TS) and TiO2/Fe2+/sonolysis (TFS). In the case of the sonophoto-Fenton process, the IBP degradation (95%) and mineralization (60%) were attained with photo-Fenton (FH). The presence of ultrasonic irradiation slightly improves the iron catalytic activity. On the other hand, total removal of IBP and elimination of more than 50% of dissolved organic carbon (DOC) were observed by photocatalysis with TiO2 in the presence of ultrasound irradiation (TS). In contrast only 26% of mineralization was observed by photocatalysis with H2O2 (TH) in the absence of ultrasound irradiation. Additional results showed that, in the TFS system, 92% of DOC removal and complete degradation of IBP were obtained within 240 min of treatment. The advanced oxidation hybrid systems seems to be a promising alternative for full elimination/mineralization for the recalcitrant micro-contaminant IBP.